The United States and the Events of 1965–1966 in Indonesia - E. N. Glazunova; A. S. Manykin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In 1965–1966 Indonesia experienced mass killings of communists and Leftists, as well as ethnic Chinese, who were thought to be members of pro-communist organizations. These bloody events opened the most active phase of change of power in Indonesia, marked the beginning of the ‘new order’ period, and paved the way to the 1968 ouster of the President Sukarno, whom the United States had long been displeased with, and the ascension to power of the General Suharto, who would rule the country for the next three decades. Despite the fact that Indonesia faced a severe domestic political conflict, involment of external actors, primarily the United States, has never been questioned by the historians. However, due to a lack of primary sources, it has been difficult to determine the extent of this involvement. This paper is based on a close examination of recently declassified (and published in the U.S.) materials, mainly the reports of American diplomats from Jakarta and other Indonesian regions. The authors characterize U.S. position towards the aforementioned events in Indonesia and explain the Johnson administration’s choice of the intensity level and particular tools of involvement in the conflict. The conclusion is drawn that the U.S. government maintained close ties with the leadership of the Indonesian military, initially welcomed the General Suharto’s efforts aimed at ousting President Sukarno, encouraged the repressions and led a broad information-psychological campaign using the CIA playbooks. The intensity of these actions was much lower than in Indochina or the Dominican Republic but in specific local conditions in Indonesia characterized by high level of political violence, the tactics chosen by the U.S. sufficed to deliver a devastating blow to the Leftist movement and to oust the Predisent Sukarno.